Spicer and Pegler's book-keeping and accounts - Spicer, E.E.; Pegler, Ernest Charles; Gee, Paul. (London : Butterworths, 1988)
This edition has been completely updated to cover recent developments in fixed asset accounting, including revaluations, goodwill, merger accounting, long-term contracts, deferred tax, off-balance sheet finance, extraordinary items and accounting for price changes.
Previous ed.: 1999.
Includes index.
ne 10/07/2019
Loans
Keywords: Accounting; Bookkeeping